1964
DOI: 10.2172/4114311
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration Disposal of High-Level Radioactive Solids in Lyons, Kansas, Salt Mine: Background and Preliminary Design of Experimental Aspects

Abstract: This document contains informotion of a preliminary nature and was prepared primarily for internal use at the Oak Ridge National Laboratory. It is subject to revision or correction and therefore does not represent a final report. The information is not to be abstracted, reprinted or otherwise given public dissemination without the approval of the ORNL patent bronch. Legal and Information Control Department. LEGAL NOTICE This report was prepared as an account of Government sponsored work. Neither the United Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1968
1968
1996
1996

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The experiments conducted during 1961-1962 at the Carey salt mine revealed that it was impractical to dispose of liquid HLW wastes in salt because of questions about vaporization, loss of containment, and M o n s with the rock (Bradshaw et al, 1964). Even before these experiments, consideration was given to solidification of reprocessing liquid HLWs by means such as vitrification.…”
Section: Disposal Conceptsmentioning
confidence: 99%
See 4 more Smart Citations
“…The experiments conducted during 1961-1962 at the Carey salt mine revealed that it was impractical to dispose of liquid HLW wastes in salt because of questions about vaporization, loss of containment, and M o n s with the rock (Bradshaw et al, 1964). Even before these experiments, consideration was given to solidification of reprocessing liquid HLWs by means such as vitrification.…”
Section: Disposal Conceptsmentioning
confidence: 99%
“…With successful efforts at ORNL and Hanford to convert liquid HLW into solids for geologic disposal (see Appendix A), in 1962 the AEC requested ORNL to conduct a demonstration test in a suitable salt formation in an effort to establish the practicality of using salt deposits for the disposal of solidified wastes. The engineering and scientific objectives of this test included (1) the demonstration of waste-handling equipment and techniques; (2) the determination of gross effects of radiation (up to lo7 gray) on factors such as hole closure, floor uplift, and salt-pillar deformation within a temperature range of 100" to 200" C; (3) the determination of the radioIytic production of chlorine; and (4) the collection of data on the plastic flow of salt at elevated temperatures (Bradshaw et al, 1964). The latter information was to be used in the design of an actual disposal facility.…”
Section: Project Salt Vaultmentioning
confidence: 99%
See 3 more Smart Citations